ANALISIS PERFORMASI WIRELESS MESH MENGUNAKAN PROTOKOL HYBRID WIRELESS MESH PROTOCOL (HWMP) PADA JARINGAN MOBILE AD HOC NETWORK(MANET) - Muhammad Darman Saleh; Muh. Yamin; LM Fid Aksara (semanTIK, 2019)
The growing development of wireless technology in communication between users requires high-quality networks. This study aims to design a network and as a test parameter on the Wireless Mesh Network (WMN) using the routing protocol Hybrid Wireless Mesh Protocol (HWMP). This network is connected by using several access points that have been modified using OpenWRT software. The test parameters to be carried out are by testing the performance of the HWMP routing protocol in self-configure and self-healing as well as some supporting data from Throughput and Jitter. The data generated by using several access points and two (2) users produce data whereon self-configure can be done very quickly, unlike the case with self-healing which requires more time, the effect of inadequate access point location gives rise to network performance, not yet maximal, the existence of routing HWMP affects Throughput and Jitter generated by the user if the exchange of information in the condition always changes from one place to another. The average result of self-configuration is 100 bytes / 64ms, self-healing is 100 bytes / 187ms. Users of bandwidth 1 and 2 are 5,930 Kbyte / s and 5,210,170 Kbyte / s. Jitter values for users 1 and 2 are 1.554 ms and 1,699 ms. Throughput on users 1 and 2 is 0.283 Mbit / s and 4 Mbit/s. Keywords—WMN, HWMP, Firmware openWRT, Self-Configure, Self-Healing DOI : 10.5281/zenodo.3233134